1992
DOI: 10.1002/crq.3900100107
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐child mediation: An empirical assessment

Abstract: The relationship among preintervention family functioning, conflict characteristics, and mediation outcome and subsequent family functioning was assessed in seventy parent‐child disputes. The Family Environment Scale (FES) profiles indicated that families were distressed, with high levels of dysfunction. Parents and adolescents had divergent perceptions of the conflict. Parental perception, especially that of mothers, was of greater seriousness of the problem related to positive mediation outcome. Positive cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…There were no significant differences between mothers and fathers or boys and girls. Evaluations of overseas parentadolescent mediation programs generally report that two thirds to three fourths of respondents rate their experience as moderately to highly successful (Phear & Shaw, 1989;Van Slyck et al, 1992). Similar results are reported in the family therapy literature (Kazdin, 1991).…”
Section: Satisfaction Witfi Outcome and Servicesupporting
confidence: 72%
“…There were no significant differences between mothers and fathers or boys and girls. Evaluations of overseas parentadolescent mediation programs generally report that two thirds to three fourths of respondents rate their experience as moderately to highly successful (Phear & Shaw, 1989;Van Slyck et al, 1992). Similar results are reported in the family therapy literature (Kazdin, 1991).…”
Section: Satisfaction Witfi Outcome and Servicesupporting
confidence: 72%
“…Mediation between divorcing parents has been found to yield modest gains in cooperation (Pearson and Th oennes 1989) and to decrease confl ict and improve communication (Benjamin and Irving 1995). Child custody mediation has also been shown to have a twelve-year durable eff ect on parental involvement in children's lives (Emery et al 2001), and parentchild mediation has resulted in improved family relationships three months following mediation ( Van Slyck, Stern, and Newland 1992). Th ese studies indicate the potential of mediation to improve relationships between parties and in families more generally, providing support for the claim that the process can improve participants' ability to manage confl ict and maintain good relationships with others-even family members who were not present in the mediation.…”
Section: Conceptualizing and Measuring Mediation Successmentioning
confidence: 99%
“…Several studies in the context of court‐connected, community, and family mediation have found an ambiguous relationship between short‐ and long‐term mediation effects (Van Slyck, Stern, and Newland ; Pruitt et al ; Emery, Matthews, and Kitzmann ; Donnelly and Ebron ; Kaiser and Gabler ). A study by Peter Kaiser and Andrej Marc Gabler (2014) on court‐connected mediation showed a positive relationship between short‐term and long‐term satisfaction with the mediation experience.…”
Section: The Importance Of Studying Long‐term Mediation Effectivenessmentioning
confidence: 99%
“…In previous studies, data were collected from three months (Van Slyck, Stern, and Newland ) to three years after the mediation (Donnelly and Ebron ). In our current study, we chose an intermediate time lag of one year (De Cuyper et al ; Kaiser and Gabler ), allowing enough time for the results of the agreement to be felt, while reducing the likelihood that conflict parties would forget about the mediation or that parties would become unreachable (i.e., move away) (Pruitt et al ).…”
Section: The Importance Of Studying Long‐term Mediation Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation